Biodegradation of Oil Palm Empty Fruit Bunch Waste by Pleurotus ostreatus and Volvariella volvacea Using Solid-State Fermentation - Umi Nur Jannah; Dewi Chusniasih; Erma Suryanti; Khaerunissa Anbar Istiadi (Universitas Labuhanbatu, 2025)
Background: Oil palm empty fruit bunches (OPEFB) represent the largest form of solid waste generated from palm oil production, comprising approximately 23 % of the weight of every ton of fresh fruit bunches (FFB) processed. Untreated OPEFB waste causing pollution problems and increase toxicity due to methane emission. This study aims to evaluate the potential of OPEFB as a growth substrate for the cultivation of Pleurotus ostreatus and Volvariella volvacea, as well as to assess the reduction in lignocellulosic content following fungal biodegradation. Methodology: The experiment was conducted using solid-state fermentation (SSF), and lignocellulose content was analyzed using the Chesson method and SNI 0429:2008 through descriptive quantitative analysis. Findings: Over a 21-day incubation period, mycelial growth of both fungi successfully colonized the OPEFB baglogs, resulting in a 1–2 % reduction in baglog weight. Both P. ostreatus and V. volvacea demonstrated the ability to degrade lignocellulose by secreting lignin peroxidase (LiP), manganese peroxidase (MnP), laccase, cellulase, and hemicellulase enzymes. Initial lignocellulose levels of OPEFB were 18 % lignin, 57 % cellulose, and 20 % hemicellulose. After 21 days of incubation, P. ostreatus reduced these levels to 10 % lignin, 47 % cellulose, and 19 % hemicellulose, while V. volvacea reduced them to 11 % lignin, 52 % cellulose, and 18 % hemicellulose. Contribution: These findings indicate that OPEFB is a viable substrate for mushroom cultivation and can be effectively biodegraded by these fungi, offering a sustainable approach to managing palm oil industry waste. The treated OPEFB can be used as organic fertilizer, animal feed, and briquettes